Profiling catalase gene expression in Drosophila melanogaster during development and aging. - Klichko, V.I.; Radyuk, S.N.; Orr, W.C. (Archives of Insect Biochemistry and Physiology, 2004)
Catalase represents one of the key antioxidant enzymes (AOE) in the metabolism of oxygen free radicals. A comprehensive analysis was brought to bear on establishing catalase gene expression profiles during development and aging, with the underlying objective being to identify potential regulatory factors. Expression of the catalase gene exhibits substantial variations during development and aging in a stage- and tissue-specific manner. At the temporal level, previous observations of the coincidence of ecdysteroid pulses with peaks in catalase expression during developmental stages were largely corroborated. In adults, a small but significant decline in catalase expression was noted in adults as a function of age. Spatially, it was ascertained that catalase expression is mostly confined to tissues related to intermediary metabolism, digestive and adipose systems as well as oenocytes. By combining histochemical analysis of reporter gene expression with immunostaining of the endogenous product, it was possible to identify putative positive and negative regulatory elements that control catalase expression. Finally, when adult flies were subjected to various environmental insults, such as heat, paraquat, hyperoxia and H(2)O(2), no significant responses were observed, suggesting that catalase gene expression is largely governed by intrinsic genetic programs.